Óptimo despliegue de generación distribuida en base a análisis de fallas en sistemas de distribución - Burbano Vásquez, Byron Andrés (2018)
The document presents an optimal location of distributed generation units (DG) based on unbalanced three phase fault analysis. Unbalanced faults can be classified in line-to-earth fault, line-to-line fault and two lines-to-earth to ground fault. Additionally, another restriction is associated with voltage drop in the entire network. The deployment of DG units into the distribution grid will modify the network´s topology, and thus, large short-circuit currents will flow from generator terminals into the fault. Set in this context, the restriction associated with the deployment of DG is based on that short circuit interrupting devices such as circuit breakers, disconnectors and fuses should operate within their ratings. The proposed methodology is implemented in the IEEE radial distribution test feeder. The first scenario considers a traditional network, in these scenario no introduction of distributed generation. This scenario establishes the short-circuit currents, that are used as preliminary values to determine the system's restrictions. The second scenario contemplates the deployment of DG based on a mathematical model, which considers the restrictions imposed by the initial system (nominal rating of power components). The results permit to determine the optimal placement of DG that satisfy with all restrictions, and optimize the operation of the distribution system.